2017
DOI: 10.1007/s13193-017-0718-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Treatment for Medullary Thyroid Carcinoma—a Single Centre Experience

Abstract: We conducted this study to evaluate the demography, clinical presentation, management and outcomes of medullary thyroid carcinoma (MTC) from the Indian context. This was a retrospective study of patients with MTC managed between January 2008 and December 2016. All pertinent data was collected and the results were analysed using STATA (v.13.1). MTC accounted for 90/2022 (4.45%) patients managed with thyroid cancer during the study period. The mean age of presentation was 40 years (range 14-70 years) with 47 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…from Pisa, Italy concluded that most of the MTCs are diagnosed in a subject with a thyroid nodule, either single or in the context of multinodular goiter, without any other specific symptom; however, untreatable diarrhea and/or flushing can be present in very few mostly advanced cases ( 14 ). A study from India showed goiter with cervical lymphadenopathy was the most common presenting symptom seen in 67% of patients in their cohort ( 15 ). In another Southeast Asian study, 81.2% of the study patients presented with goiter.…”
Section: Discussionmentioning
confidence: 99%
“…from Pisa, Italy concluded that most of the MTCs are diagnosed in a subject with a thyroid nodule, either single or in the context of multinodular goiter, without any other specific symptom; however, untreatable diarrhea and/or flushing can be present in very few mostly advanced cases ( 14 ). A study from India showed goiter with cervical lymphadenopathy was the most common presenting symptom seen in 67% of patients in their cohort ( 15 ). In another Southeast Asian study, 81.2% of the study patients presented with goiter.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of metastasis were highest in bones followed by lungs and liver (12.5%, 9.4% and 3.1%, respectively), while a study by Cherian AJ et al . [ 15 ] showed that the most common site of metastasis is lung, followed by bone and liver. The studies conducted by S. Roman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery is uniformly recommended to treat various types of MTC, the clinicopathological characteristics of SMTC and hereditary MTC are distinct. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Although surgery is uniformly recommended to treat various types of MTC, the clinicopathological characteristics of SMTC and hereditary MTC are distinct. 4,5 Presently, the American Thyroid Association Guidelines, the United Kingdom National Multidisciplinary Guidelines for the management of thyroid cancer, and several different individual investigators all recommend total thyroidectomy and central lymph node dissection for patients with MTC. 3,4,6,7 However, the benefit of prophylactic lateral lymph node dissection remains controversial.…”
Section: Introductionmentioning
confidence: 99%